"Vascular Memory” as a predictive factor for endothelium function-associated conditions : Comparative study of 3 clinical models – Raynaud’s Disease, Systemic Sclerosis and Diabetes Mellitus - Amaral, Marta Sofia Carapeto (2024)
Abstract Introduction: Systemic sclerosis (SSc) is an autoimmune connective tissue disease characterized by small vessel vasculopathy, autoantibody production and collagen deposition in the skin and internal organs. Although SSc is considered a fibrosing disease, vascular involvement together with immune activation, inflammatory response and oxidative stress seem to play major roles in the pathogenesis of organ dysfunction. There is some evidence that endothelial dysfunction may precede the typical perivascular abnormalities present in the disease, with the microvasculature becoming aberrant and exhibiting dilations, tortuosities and microhaemorrages, with extense avascular areas, resulting in tissular hypoxia, but the published data are still controversial. Despite the phenotypic variety, almost all patients with systemic sclerosis have Raynaud's phenomenon (RP), an episodic vasospastic ischaemic disorder. Raynaud's phenomenon can precede other symptoms and signs of systemic sclerosis by up to 30 years, but its presence alone is not sufficient for the development of SSc. Therefore, it has been particularly difficult to understand what mechanisms come first in the pre-clinical phase of systemic sclerosis, as it is a rare disease with a small direct genetic impact. Nevertheless, studying the offspring of these patients could be the closest to a control group for genetics and early in life (at least) environmental factors. This thesis was developed from the hypothesis that a ‘vascular memory’ characterized by anatomical microcirculatory changes, could be the earliest manifestation and the influencing factor for endothelial dysfunction. Methods: The study included patients with systemic sclerosis, n=124, two different endothelium dysfunction-associated diseases (disease control groups): Raynaud’s disease (RD), n=158, and type 2 diabetes mellitus (T2DM), n=98, and their respective healthy offspring (SSc offspring, n=55, RD offspring, n=11, T2DM offspring, n=50), and healthy controls (n=59). All the groups were studied concerning the demographic, clinical and general biochemical features. Circulatory anatomy was studied using Nailfold VideoCapillaroscopy (NVC) and the characterisation of the inflammation, immune activation and oxidative stress was addressed by the quantification of VCAM-1, ICAM-1, VEGF-A, 3-NT and TAC. Main findings: The healthy offspring of patients with SSc showed significant changes in NVC when compared to controls [number of capillaries per field inferior to eight (p=0.003), enlarged capillaries (p=0.003), major morphologic abnormalities (p=0.027), oedema (0.031), avascular areas (p<0.001), neoangiogenesis (p=0.041), reduced velocity of blood flow (p<0.001), sludge (p<0.001)], despite having normal levels of VCAM-1, ICAM-1, VEGF and 3-NT, with a high level of TAC. When compared to the patients with SSc, their offspring had similar changes regarding major morphologic abnormalities (p=0.6), “sludge” (p=0.06) and avascular areas (p=0.78). This two groups showed differences only in capillaries per field (p<0.001), enlarged (p<0.001) and giant (p<0.001) capillaries, minor dysmorphias (p<0.001), haemorrhages (p<0.001) and interstitial oedema (p<0.001). Capillary rarefaction and “sludge” were even more pronounced in the offspring of SSc when compared to patients with RD (p<0.001 for both parameters). Patients with RD differed from controls only in the number of enlarged capillaries (p=0.02), blood flow (p=0.002) and neoangiogenesis (p=0.04); their offspring had a practically normal NVC. Regarding the biologic products, none were higher in the RD and respective offspring group compared to controls. The offspring of patients with T2DM also showed significant differences from controls in NVC [edema (p=0.009), avascular areas (p<0.001), neoangiogenesis p=0.001, and reduced blood flow (p=0.046)]. There was only difference in haemorrhages (p=0.002) between patients with T2DM and their offspring. The T2DM offspring group had serum levels of 3-NT higher than controls (p=0.027). Conclusions: The anatomy of microvasculature in the offspring of patients with SSc appears to change before the immune system and inflammation markers get activated. This may be due to the fact that the microcirculatory structure is genetically driven whilst the disease onset may need further “hits” to develop. RD might have a different physiopathology from RP in the context of SSc, highlighting the different nature of the two conditions regarding their early (pre-clinical) mechanisms. The offspring of patients with T2DM showed the same phenomena that the SSc group, (despite the differences in the terminal vessels morphology), suggesting the presence of a genetic-based background which may develop into the metabolic disease after exposure to other stimuli. Therefore, we may postulate the existence of a ‘vascular anatomical memory’ in systemic sclerosis.